ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PENYERAPAN ANGGARAN DENGAN VARIABEL INTERVENING EFEKTIVITAS ANGGARAN BERBASIS KINERJA PADA DINAS KESEHATAN PROVINSI BANTEN - sulthony, akbar (Pascasarjana Universitas Sultan Ageng Tirtayas, 2021)
Delay in budget absorption is a classic problem in government agencies that generally occurs in the first trimester and swells at the end of the year Some of the fundamental causes of low budget absorption include the preparation process for the implementation of an immature budget, preparation of budget absorption plans is less accurate, and a late auction process. This study aims to determine the relationship of understanding, training, external pressure on budget absorption with intervening variables on the effectiveness of performance-based budgeting. The study population was 55 Provincial Health Department employees. Data analysis was performed using the Structural Equation Model (SEM) method using PLS. From the results of the hypothesis test, it can be concluded that 1) Understanding has a positive effect on budget absorption, so the higher understanding an employee has regarding budget planning, the higher the level of budget absorption, 2) Training has a positive effect on budget absorption, so that more training is ever followed by an employee related to budget planning institutions, the higher the level of budget absorption, 3) External pressure does not affect the absorption of the budget, 4) Understanding has a positive effect on the effectiveness of performance-based budgeting, so the higher the understanding of an employee related to budget planning institutions will the higher the effectiveness of performance-based budgeting, 5) Training has a positive effect on the effectiveness of performance-based budgeting, so that more training is ever attended by an employee related to the agency's budget planning. the higher the effectiveness of performance-based budgeting, 6) External pressure does not affect the effectiveness of performance-based budgeting, and 7) The effectiveness of performance-based budgeting has a positive effect on the absorption of the budget, so the more effective the performance-based budget that is applied the higher the level of budget absorptionÂ